A sequence is defined recursively by a1=1,an=(an-1+1)^2. Write the first

  1. A sequence is defined recursively by a1=1,an=(an-1+1)^2. Write the first 4 terms of the sequence.
    1. answers icon 3 answers
    2. jenny asked by jenny
    3. views icon 3,015 views
  2. Let {An} be the sequence defined recursively by A1=sqr(2) and A(n+1) = sqr(2+An) for n is bigger and equal to 1. Show that An <
    1. answers icon 0 answers
    2. Belle asked by Belle
    3. views icon 1,239 views
  3. how do I write the first five recursively defined sequence of this problem a(n)=-2?please help and explain with steps
    1. answers icon 6 answers
    2. mikey asked by mikey
    3. views icon 559 views
  4. Reiny can you please help with these 3 problem. 1. a1=-4;an-1-3 this is find the first five terms of the recursively defined
    1. answers icon 3 answers
    2. mikey asked by mikey
    3. views icon 675 views
  5. Write the first five terms of the sequence defined recursively. Use the pattern to write the nth term of the sequence as a
    1. answers icon 1 answer
    2. leah asked by leah
    3. views icon 666 views
  6. A sequence is defined recursively by the following rules:f(1)=3 f(n+1)=2⋅f(n)−1 Which of the following statements is true
    1. answers icon 1 answer
    2. carmen asked by carmen
    3. views icon 1,113 views
  7. this is a difficult question for me please help! thankyouA sequence is defined recursively by an + 1 = 3an − n, a1 = 2. Find
    1. answers icon 0 answers
    2. lene asked by lene
    3. views icon 635 views
  8. this is a difficult question for me please help! thankyouA sequence is defined recursively by an + 1 = 3an − n, a1 = 2. Find
    1. answers icon 1 answer
    2. lene asked by lene
    3. views icon 4,683 views
  9. A geometric sequence is defined recursively as a1=2/3, an+1=an×1/2What is the explicit formula for the sequence? (1 point)
    1. answers icon 1 answer
    2. Hana asked by Hana
    3. views icon 73 views
  10. A sequence is defined recursively by the following rules:f(1)=3 f(n+1)=2⋅f(n)−1 Which of the following statements is true
    1. answers icon 1 answer
    2. Jean asked by Jean
    3. views icon 3,198 views